Cartilha de acessibilidade na web: como construir um site para a Biblioteca Pública Municipal Ney Pontes Duarte da cidade de Mossoró/RN - Santos, Rosa Milena dos (2023)
We live in a digital-native society where information flows through various means, forms, and platforms with the aim of informing people who come into contact with it, requiring it to be accessible to everyone in both physical and digital mediums. Therefore, the question of this research is to understand how the Ney Pontes Duarte Municipal Public Library in Mossoró, Rio Grande do Norte, Brazil, can contribute to providing accessible information to increase interaction with its users through web accessibility. The general objective of this study is to produce a guidebook demonstrating the construction of an accessible website for the Ney Pontes Duarte Municipal Public Library in Mossoró, addressing aspects of web accessibility. The specific objectives are to discuss theoretical aspects of Information Science and web accessibility, seeking best practices reported in the literature; to develop a guidebook for the construction of an accessible website for the Ney Pontes Duarte Municipal Public Library in Mossoró, Rio Grande do Norte; to assist the public library in offering web-based services for people with disabilities, serving as a model for other information units. Methodologically, this is a bibliographic research, as well as a case study with a descriptive and exploratory objective, applied in nature with a qualitative approach. The final product of this professional master’s degree was the creation of a guidebook on web accessibility for the public library in Mossoró, aiming to provide a guide for the construction of an accessible website for this information unit. It is understood that there are difficulties in building an accessible website for the library, considering that its staff does not have the necessary expertise, starting with the lack of a librarian position. The study’s product will be handed over to the library for future implementation and to serve as a reference for web accessibility in the public sector. It is hoped that other public libraries can use this guidebook as a foundation to become innovative, modern, inclusive, and accessible on the web.